Atypical Metastases from Prostate Cancer: Alpha-Methylacyl-Coenzyme A Racemase (AMACR) as a Potential Molecular Target in Prostate-Specific Membrane Antigen-Negative Prostate Adenocarcinoma - Ilham Badrane; Angelo Castello; Matteo Brunelli; Corrado Cittanti; Sara Adamantiadis; Ilaria Bagni; Noemi Mindicini; Federica Lancia; Massimo Castellani; Licia Uccelli; Mirco Bartolomei; Luca Urso (Biomolecules)
Prostate cancer (PCa) is a high-prevalence disease usually characterized by metastatic spread to the pelvic lymph nodes and bones and the development of visceral metastases only in the late stages of disease. Positron Emission Tomography (PET) plays a key role in the detection of PCa metastases. Several PET radiotracers are used in PCa patients according to the stage and pathological features of the disease, in particular 68Ga/18F-prostate-specific membrane antigen (PSMA) ligands. Moreover, 2-deoxy-2-[18F]fluoro-D-glucose 18F-FDG PET usually shows metastases in the late stages of disease, when dedifferentiated neoplastic clones lose PSMA expression. In some cases, PCa patients may present atypical sites of metastases, with uncommon appearance at PET imaging with different radiotracers. We present the case of a patient with biochemical recurrence of PCa (ISUP Grade Group IV; PSA 4.7 ng/mL) showing atypical sites of metastases (the testis and multiple lung nodules) with absent PSMA expression and high [18F]FDG avidity. The patient showed diffuse positivity to alpha-methylacyl-coenzyme A racemase (AMACR). Moreover, a literature review was performed by collecting cases of PCa patients with atypical metastatic spread detected via PET imaging, with the aim of highlighting the relationship between atypical sites of metastases, imaging presentation, and pathology findings.